Analisis Penerapan Sentralisasi Fungsi Akuntansi dan Keuangan dalam Perusahaan Holding: Studi Kasus PT Semen Indonesia (Persero) Tbk - Sigit Suhartono; Mukhamad Ikhwan Hadi; Moh. Agung Surianto (UniSadhuGuna Business School, 2023)
PT Semen Indonesia (Persero) Tbk. (SIG) is one of the state-owned companies that since 2013 has transformed into a Strategic Holding. SIG has 17 Subsidiaries (AP), consisting of 8 Cement Making companies and 9 non Cement Making companies. Of the Cement Making Companies, 3 APs whose share ownership is 99.9% owned by SIG, namely PT Semen Padang, PT Semen Tonasa and PT Semen Gresik. This research was conducted at PT Semen Indonesia (Persero) Tbk. (SIG). The objectives of this study are (1) analyzing the implementation of Policies & SOPs at PT SIG, (2) Effectiveness of the implementation of centralization of Accounting & Finance functions at PT SIG. The basic method used is descriptive with the implementation of case studies. Data collection was carried out by interview, observation, Forum Group Discuss (FGD) and documentation methods. The results showed that the implementation of Holding Policies & SOPs in Subsidiaries (AP) has been implemented well based on periodic reviews and as an effort to create added value for the group, efficiency, and better performance of SOEs.